ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI PERTUMBUHAN LABA PERUSAHAAN PT. HANJAYA MANDALA SAMPOERNA TBK PERIODE 2017-2021 - Tiar Lina Situngkir; Dilla Agiel Dwi Aprilia; Fifi Nurul Rahman; Neng Lala Komala; Rahmat Hidayat; Rizal Zidane (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The purpose of this research is to evaluate the financial performance of PT. Hanjaya Mandala Sampoerna Tbk for the 2017-2020 season. This research was conducted using quantitative descriptive analysis and the Du Pont system was used as a method, namely calculating the ratio of NPM, TATO, ROA, EM, ROE. The data source used in this study comes from secondary data, namely financial report data published through idx.co.id in the form of income statements for 2017-2021. The results showed that PT Hanjaya Mmandala Sampoerna Tbk underwent adjustments from 2017 to 2019, but the company's performance decreased in 2020 and 2021.